Women's Homelessness: International Evidence on Causes, Consequences, Coping and Policies - Guy Johnson; David C. Ribar; Anna Zhu (Institute of Labor Economics (IZA), 2017)
This paper reviews international evidence regarding women's homelessness. It discusses different definitions of homelessness and how women are frequently part of the "hidden homeless" population and less a part of the unsheltered homeless population. It also considers the data that are used to enumerate and study homeless people. The structural, personal, and random causes of homelessness are discussed, with evidence pointing to highly gendered patterns. The paper also describes the consequences of women's homelessness, including the consequences for children, and the material and psychological coping strategies that homeless people employ. It considers policies to reduce homelessness and ameliorate its problems.
Keywords: I30; R31; 330; policies; hidden homeless; children; women; homelessness; coping strategies